Cyclic behavior of precast. - Ou, Yu-Chen
The cyclic behavior of precast segmental concrete bridge columns with high performance (HP) steel reinforcing bars and that with conventional steel reinforcing bars as energy dissipation (ED) bars were investigated. The HP steel reinforcing bars are characterized by higher strength, greater ductility and superior corrosion resistance compared with the conventional steel reinforcing bars. Three large scale columns were tested. One was designed with the HP ED bars and two with the conventional ED bars. The HP ED bars were fully bonded to the concrete. The conventional ED bars were fully bonded to the concrete for one column, whereas unbonded for a length to delay fracture of the bars and to increase energy dissipation for the other column. Test results showed that the column with the HP ED bars had greater drift capacity, higher lateral strength, and larger energy dissipation than that with fully bonded conventional ED bars. The column with unbonded conventional ED bars achieved the same drift capacity and similar energy dissipation capacity as that with the HP ED bars. All the three columns showed good self centering capability with residual drifts not greater than 0.4 percent drift. An analytical model referred to as joint bar slip rotation method for pushover analysis of segmental columns with ED bars is proposed. The model calculates joint rotation from the slip of the ED bars from two sides of the joint. Good agreement was found between analytical predictions and the envelope responses of the three columns.
Keywords: Precast concrete; Prestressed concrete; Segmental construction; Bridge columns; Self-centering.; High-performance steel reinforcing bars